Synergistic Combination of AS101 and Azidothymidine against Clinical Isolates of Carbapenem-Resistant Klebsiella pneumoniae - Chung-Lin Sung; Wei-Chun Hung; Po-Liang Lu; Lin Lin; Liang-Chun Wang; Tsung-Ying Yang; Sung-Pin Tseng (Pathogens, 2021)
Owing to the over usage of carbapenems, carbapenem resistance has become a vital threat worldwide, and, thus, the World Health Organization announced the carbapenem-resistant Enterobacteriaceae (CRE) as the critical priority for antibiotic development in 2017. In the current situation, combination therapy would be one solution against CRE. Azidothymidine (AZT), a thymidine analog, has demonstrated its synergistically antibacterial activities with other antibiotics. The unexpected antimicrobial activity of the immunomodulator ammonium trichloro(dioxoethylene-o,o’)tellurate (AS101) has been reported against carbapenem-resistant Klebsiella pneumoniae (CRKP). Here, we sought to investigate the synergistic activity between AS101 and AZT against 12 CRKP clinical isolates. According to the gene detection results, the blaOXA-1 (7/12, 58.3%), blaDHA (7/12, 58.3%), and blaKPC (7/12, 58.3%) genes were the most prevalent ESBL, AmpC, and carbapenemase genes, respectively. The checkerboard analysis demonstrated the remarkable synergism between AS101 and AZT, with the observable decrease in the MIC value for two agents and the fractional inhibitory concentration (FIC) index ≤0.5 in all strains. Hence, the combination of AS101 and azidothymidine could be a potential treatment option against CRKP for drug development.